Individual and Interactive Effects of Temperature and Watering Regime on Canola Growth and Physiological Characteristics - McDormand, Emma D.; Qaderi, Mirwais M. (Plant-environment interactions (Hoboken, N.J. : 2018), 2025)
ABSTRACT Although many studies have considered the effects of temperature and water on plants, the combined effects of these factors on canola (Brassica napus) growth, physiological traits, and fatty acids require more attention. Canola is an important oilseed crop in Canada and around the world and fatty acids act as regulators of stress signaling. We grew plants under two temperature regimes (22°C/18°C and 28°C/24°C; 16 h light and 8 h dark) and two watering regimes (well‐watered and water stressed) in controlled‐environment growth chamber for 3 weeks after 1 week of initial growth under 22°C/18°C. We measured growth, biomass, photosynthesis, fatty acids, and other physiological traits of plants. With respect to plant growth and physiological traits, as individual factor, higher temperatures decreased stem diameter, specific leaf mass, leaf water potential, and flavonoids, whereas water stress decreased stem height and diameter, leaf area and number, leaf mass, net CO2 assimilation, transpiration, and stomatal conductance, but increased leaf mass ratio (leaf dry mass/plant dry mass). In terms of interaction, higher temperatures increased plant biomass, chlorophyll (Chl) a, carotenoids, and total Chl in the well‐watered plants, but decreased all these traits in the water‐stressed plants. With respect to fatty acids as individual factor, higher temperatures decreased tricosanoic acid (C23:0), but increased heptadecanoic acid (C17:0). In terms of interaction, higher temperatures decreased cis‐10‐heptadecenoic acid (C17:1), elaidic acid (C18:1), arachidic acid (C20:0), and cis‐11,14‐eicosadienoic acid (C20:2) in the water‐stressed plants. Lower temperatures also decreased C17:1, C18:1, and C20:2 in the water‐stressed plants. Overall, palmitoleic acid (C16:1) was higher in the stem than in the leaf. This study revealed that higher temperatures combined with water stress decreased some physiological traits and fatty acids and, in turn, plant biomass. Further studies are required to determine the effects of multiple climate change components on fatty acids in canola and other oilseed crops. This study revealed that higher temperatures combined with water stress decreased some physiological traits and fatty acids and, in turn, plant biomass.